Reviewing the "WelfareState" in Local Governments Around the Capital City of the Archipelago - Suwardi Sagama (Jurnal Hukum Prasada, 2025)
Regencies/cities in East Kalimantan are still far from fulfilling welfare, because the availability of infrastructure is uneven and public services are constrained by distance. Regional expansion is expected to solve welfare problems, but it has not yet provided welfare. Since East Kalimantan was designated as an IKN, the regency/city area as well as a buffer area of the IKN strives to meet the welfare that has not been fulfilled. Usingnormative-empirical legal research methods, normative research found that Law 23/2014 on Regional Government has regulated the realization of welfare through regional expansion more comprehensively than the previous regulations on local government. Meanwhile, empirically, the buffer regional government around the IKN still has problems in public services and infrastructure that directly affect the welfare of the community.